Implantação do exame do reflexo vermelho em crianças da região do hospital das Clínicas da Faculdade de Medicina de Botucatu-SP-Brasil - Rodrigues, Antonio Carlos Lottelli [UNESP]; Prado, Rodrigo Bueno [UNESP]; Miguel, Licério [UNESP] (FapUNIFESP (SciELO), 2012)
Purpose: To describe the implantation of the red reflex test in 30 cities in the area of Botucatu Medical School Clinical Hospital, (480,337 inhabitants) and the creation of a reference Center for children with red reflex changes, the Red reflex screening and another Center for treatment of childhood cataract. Methods: The red reflex exam was released in 30 cities of the surrounding Botucatu area, lectures were done in the cities invited to participate by the Regional Department of Health.109 pen torch ophthalmoscopes were distributed to the hospital maternities and primary care units. The Red reflex screening attended cases of altered or doubtful red reflex and established the diagnosis. The Center for treatment of childhood cataract performed the preoperative examination, surgical treatment and follow-up of children with cataracts. Results: After one year the Red reflex screening attended 29 children, 17 males and 12 females, mean age and pattern deviation (PD) of 10.09 ± 20.35 months (7 days-98 months old). 16 patients were referred with altered red reflex, with a mean age and pattern deviation of 13.17 ± 24.14 months (7 days-98 months old). The alteration was confirmed in all of these cases. 13 children had cataract. In 13 children with doubtful exam, with a mean age and PD of 6.29 ± 14.46 months (7 days-54 months old), the alteration was not confirmed in any of these patients. The incidence of negative red reflex found among newborns was 9.2/10,000 and the incidence cataracts in this same group was 7.9/10,000. Conclusion: We described the implantation of the red reflex exam in the Botucatu area, and the creation of a reference Center for eye examination of children with changes in the red reflex, and the creation of a reference Center for treatment of childhood cataract and difficulties.
Implementation of red reflex exam in children in the area of Botucatu Medical School Clinical hospital-São Paulo, Brazil
Keywords: Cataract/congenital; Cataract/diagnosis; Child; Ophthalmoscopes; Pupillary; Reflex